2015
DOI: 10.1186/s12974-015-0305-9
|View full text |Cite
|
Sign up to set email alerts
|

Monoacylglycerol lipase inhibitor JZL184 reduces neuroinflammatory response in APdE9 mice and in adult mouse glial cells

Abstract: BackgroundRecently, the role of monoacylglycerol lipase (MAGL) as the principal regulator of simultaneous prostaglandin synthesis and endocannabinoid receptor activation in the CNS was demonstrated. To expand upon previously published research in the field, we observed the effect of the MAGL inhibitor JZL184 during the early-stage proinflammatory response and formation of beta-amyloid (Aβ) in the Alzheimer’s disease mouse model APdE9. We also investigated its effects in proinflammatory agent - induced astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 20 publications
5
45
5
Order By: Relevance
“…In contrast, treatment of microglia with the MGLL inhibitor KML29 ( Chang et al, 2012 ) significantly lowered basal and LPS-induced prostaglandins ( Figure 2G ), as well as LPS-induced cytokine production ( Figure 2H ). These data are consistent with recent reports showing that MGLL-inactivated microglia are impaired in LPS-induced prostaglandin production and inflammatory responses ( Pihlaja et al, 2015 , Viader et al, 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…In contrast, treatment of microglia with the MGLL inhibitor KML29 ( Chang et al, 2012 ) significantly lowered basal and LPS-induced prostaglandins ( Figure 2G ), as well as LPS-induced cytokine production ( Figure 2H ). These data are consistent with recent reports showing that MGLL-inactivated microglia are impaired in LPS-induced prostaglandin production and inflammatory responses ( Pihlaja et al, 2015 , Viader et al, 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…Consistent with the absence of changes in bulk brain lipids in MAGL-MKO mice, these animals displayed no alterations in LPS-induced prostaglandin and cytokines production or microglial activation ( Figure S4A-D ). We did find, however, that cultured MAGL –/– microglia were impaired in producing prostaglandins and also displayed substantially reduced in vitro inflammatory responses ( Figure S4E and F ), consistent with recent reports (Pihlaja et al, 2015). It is possible that incomplete removal of MAGL from all brain microglia in the MAGL-MKO mice ( Figure S1E ) prevented observation of a contribution from microglia-derived MAGL to neuroinflammatory responses in vivo .…”
Section: Resultssupporting
confidence: 92%
“…Although our study design did not allow us to determine whether the MAGL-IR neurons observed in VC and C1-C2 areas were presynaptic or postsynaptic, previous electron microscopic studies reported MAGL expression on presynaptic neurons (64,65). MAGL was also found to be expressed in microglia and astrocytes and may be involved in inactivation of released ECs (66,67).…”
Section: Discussionmentioning
confidence: 83%